(untitled) (Economics and region, 2022)
The current state of the business environment of Ukraine from February 24, 2022 to April 2022 has been developed. The state and sources of filling the budget of Ukraine, the problems of functioning and loss of Ukrainian enterprises during the war are considered. Data on migration and employment of the population of Ukraine are given. The main strategic tasks of the management of enterprises in martial law to preserve their activities are formulated. It is stated that the main strategic tasks of the management of enterprises in martial law should be to maintain the manageability of the enterprise, preserve the human resources of the enterprise, and rapid adaptation and updating of business processes of the enterprise for war. Emphasis is placed on the special role of information and communication tools (various information technologies, approaches, tools and measures) in resolving enterprises from the crisis or mitigating its consequences, including due to the war. The main postulates of the Plan of Economic Revival of Ukraine, developed and proposed by the Office of the President in order to consolidate the citizens, enterprises and society of Ukraine to fight the aggressor and restore the country after the Victory.